Author's Chair in Promoting Young Learners' Speaking Skills - Jumilati, Siti; Susanto, Dias Andris; Senowarsito, Senowarsito (Universitas PGRI Semarang, 2022)
The Author’s Chair, a key component of the writer’s workshop model, provides students with the opportunity to present their written work orally, thus promoting both speaking and writing skills This activity is widely recognized for its potential to build students' confidence and enhance their speaking abilities. The theoretical framework underlying the Author's Chair is socio-constructivism, which views learning as a social process where knowledge is co-constructed through interactions with others. Socio-constructivism emphasizes the importance of social interactions in learning, where thought evolves from societal exchanges to individual understanding. This study aimed to investigate the implementation of the Author’s Chair in a kindergarten setting and to explore how this method contributes to improving young learners' speaking skills. The participants were K-2 (TK-8) students at a preschool in South Jakarta. The research employed three observation sessions, including video recordings, to examine the impact of the Author’s Chair on the students' speaking abilities. Additionally, interviews were conducted with teachers to gather their feedback on the implementation and effectiveness of the Author’s Chair in the classroom. The findings indicate that the Author’s Chair is an effective instructional tool for enhancing young learners' English-speaking skills, as it provides a platform for students to express themselves and engage in peer interactions. However, it is also evident that successful implementation requires a significant investment of time and effort from educators. In conclusion, the study suggests that the Author’s Chair can be a valuable approach in English language teaching, fostering improved speaking skills in young learners when used consistently and effectively.